Key experiments in practical developmental biology - Marí-Beffa, Manuel, 1961-; Knight, Jennifer, 1969- (Cambridge, 2005)
This is a manual of 27 laboratory exercises for courses in developmental biology. These are experiments that provided key insights into developmental questions, many of them presented by the scientists who carried out the original pioneering research. This book bridges state-of-the-art experimental work and the laboratory classes taken at the undergraduate and post-graduate levels.